Multi-omics approaches reveal that diffuse midline gliomas present altered DNA replication and are susceptible to replication stress therapy - Anastasia E. Hains; Kashish Chetal; Tsunetoshi Nakatani; Joana G. Marques; Andreas Ettinger; Carlos A. O. Biagi Junior; Adriana Gonzalez-Sandoval; Renjitha Pillai; Mariella G. Filbin; Maria-Elena Torres-Padilla; Ruslan I. Sadreyev; Capucine Van Rechem (Genome Biology, 2024)
Abstract Background The fatal diffuse midline gliomas (DMG) are characterized by an undruggable H3K27M mutation in H3.1 or H3.3. K27M impairs normal development by stalling differentiation. The identification of targetable pathways remains very poorly explored. Toward this goal, we undertake a multi-omics approach to evaluate replication timing profiles, transcriptomics, and cell cycle features in DMG cells from both H3.1K27M and H3.3K27M subgroups and perform a comparative, integrative data analysis with healthy brain tissue. Results DMG cells present differential replication timing in each subgroup, which, in turn, correlates with significant differential gene expression. Differentially expressed genes in S phase are involved in various pathways related to DNA replication. We detect increased expression of DNA replication genes earlier in the cell cycle in DMG cell lines compared to normal brain cells. Furthermore, the distance between origins of replication in DMG cells is smaller than in normal brain cells and their fork speed is slower, a read-out of replication stress. Consistent with these findings, DMG tumors present high replication stress signatures in comparison to normal brain cells. Finally, DMG cells are specifically sensitive to replication stress therapy. Conclusions This whole genome multi-omics approach provides insights into the cell cycle regulation of DMG via the H3K27M mutations and establishes a pharmacologic vulnerability in DNA replication, which resolves a potentially novel therapeutic strategy for this non-curable disease.